Analysis of the Validity Level of Biology Textbooks based on the 2013 Curriculum with the Integration of Ayat Kauniyah - Haidi, Haidi; Syafi’i, Wan; Mahadi, Imam (FKIP-Universitas Riau, 2020)
The validity of textbooks is an important thing before it is used in the learning. This study aims to determine the level of validity of the 2013 curriculum-based biology textbook that is integrated to the ayat Kauniyah (Kauniyah verses). The research was conducted on the campus of the Master of Biology Education Study Program, FKIP, Riau University. The validation of the textbook was carried out by 5 validators consisting of 3 experts according to their fields and expertise, and 2 validators from education practitioners. The validators from the expert element consists of Plant Science expert, Animal Science expert and one expertist on the integration of kauniyah verses. While the validator from the education practitioner element consists of 2 SMAIT teachers who are members of the city biology subject teacher deliberation (MGMP) Pekanbaru. The developed Biology textbooks based on the 2013 curriculum with the integration of kauniyah verses were declared very valid with an average of 95.20%. If detailed based on indicators, the results obtained are 94.44% in appearance aspects (very valid), 96.53% content aspects (very valid), 97.22% presentation aspects (very valid), 95.00% linguistic aspects (very valid) ) and aspects of the kauniyah verses 92.82% (very valid)